Effect of inner strut on mass diffusion and mixing efficiency of cross fuel jet inside the scramjet combustor. (January 2023) - Li, Z.; Leng, Jiaxuan; Abu-Hamdeh, Nidal H.; Ajour, Mohammed N.; Musa, Awad; Hatamleh, Randa I.
Abstract: Injection and mass diffusion of fuel jet released in the combustor of scramjet are the primary processes that improve scramjet engine performance. In this work, the presence of the strut fin inner the nozzle injector on the distribution and penetration mechanism of fuel jet at supersonic cross air stream is broadly investigated. The main novelty of this work is to disclose the fuel mixing mechanism inside combustion chamber with strut. Computational fluid dynamic is applied for the simulation of different nozzle types with an inner fin at high-compressible airflow. The type of injectors (3-lobe, circular and 4-lobe injector) and height of strut fin (h = 2 mm and 4 mm) are also investigated in the present research to unveil the impacts of the proposed configuration on the mixing mechanism of fuel jet. Obtained findings show that the use of the inner fin improves the mixing fuel when the strength of the produced vortex is not so high. Comparison of fuel mixing indicates that the 3-lobe injector has higher efficiency (35%) than 4-lobe and circular nozzles.